KONTRIBUSI KOMPETENSI PEDAGOGIK DAN IKLIM ORGANISASI SEKOLAH TERHADAP EFEKTIVITAS KERJA GURU - Aan Hartawan (Pascasarjana Unviersitas Majalengka, 2020)
This research is motivated by the low work effectiveness of SMK teachers, presumably due to the low pedagogical competence and the lack of conducive organizational climate. The research aims to determine: a) Pedagogical competence, school organizational climate, and work effectiveness; b) The contribution of pedagogical competence to the effectiveness of work; c) The contribution of the school organization climate to the effectiveness of work; d) The magnitude of the contribution of pedagogical competence and school organizational climate to work effectiveness. The method used was a survey with a quantitative approach, primary and secondary data were collected through questionnaires and interviews. Processing and data analysis using a statistic, the calculation process uses the SPSS program. The results showed: a) The pedagogical competence of the was good, the school organization climate was conducive, and the vocational work was quite effective, but there were still weaknesses in certain elements; b) Teacher pedagogical competence contributed to the work effectiveness of teachers by 60,99%; c) The organizational climate of the school contributes to the effectiveness of teacher work by 57,91%; d) Teacher pedagogical competence and school organizational climate together contribute to the effectiveness of teacher work by 68,90%, the remaining 31,10% is influenced by other factors not examined. In conclusion, teacher pedagogical competence and school organizational climate both partially and simultaneously contribute to the effectiveness of vocational school teachers.